The big disconnect : protecting childhood and family relationships in the digital age - Steiner-Adair, Catherine; Barker, Teresa (Harper, 2013)
Steiner-Adair offers insights and advice that can help parents achieve greater understanding, authority, and confidence as they come up against the tech revolution and how families can combat the disconnection we are experiencing from our extreme device dependence.